Enacting Service Work in a Changing World: Time for a Dialogue. (May 2021) - Subramony, Mahesh; Groth, Markus
Service work is rapidly evolving as a result of technological innovations, changing employment norms, and a variety of environmental challenges. Yet, the scope of service work scholarship appears to be restricted to traditional frontline employees occupying boundary-spanning positions in formal private-sector service organizations. Given the "perfect storm" of multiple disruptions, we believe that the time is ripe for service scholars to reexamine how service work is being (and will be) enacted in a changing world. In this editorial, we propose an expansion of the "service worker" construct, recommend a deeper exploration of the experiences of service workers, and call to situate these experiences within an evolving service work ecosystem. Our aim is to spark interdisciplinary dialogue related to service work in order to foster service scholarship and practice that are responsive to the changing world.